Molecular features of TNBC govern heterogeneity in the response to radiation and autophagy inhibition - Patrick Fischer; Maximilian Schmid; Anna Ohradanova-Repic; Rebecca Schneeweiss; Jana Hadatsch; Odysseus Grünert; Johannes Benedum; Anna Röhrer; Felix Staudinger; Philipp Schatzlmaier; Niccolo Bragato; Sandra Barna; et al. (Cell Death and Disease)
Abstract Triple negative breast cancer (TNBC) is a heterogeneous and a highly aggressive type of breast cancer. Standard of care for TNBC patients includes surgery, radio-, chemo- and immunotherapy, depending on the stage of the disease. Immunotherapy is ineffective as monotherapy but can be enhanced with taxane chemotherapy or radiotherapy. Radiation can stimulate the immune system by activating the type I interferon (IFN-I) response through cGAS-STING signaling, which recognizes cytosolic double-stranded DNA (dsDNA). Cytosolic dsDNA can be cleared by autophagy, thereby preventing activation of cGAS-STING signaling. Autophagy inhibition was therefore proposed to potentiate the immunostimulatory effects of radiation. Here we show that different molecular features of TNBC cell lines influence the effect of X-ray and carbon ion (C-ion) irradiation and autophagy inhibition on immunogenic signaling. MDA-MB-468, with low basal autophagy and high cytosolic dsDNA, activates the IFN-I response after radiation. In contrast, MDA-MB-231, characterized by high autophagy rates and low cytosolic dsDNA, induces NF-κB signaling and CXCL10 expression upon autophagy inhibition with the VPS34 inhibitor SAR405. Autophagy inhibition in TNBC cells triggers a stronger activation of innate immune cells (monocytes, natural killer cells and dendritic cells) compared to radiation. In BRCA1-mutated MDA-MB-436 cells, C-ion irradiation was more potent compared to X-rays in inducing the NF-κB-driven immunogenic response but failed to activate immune cells. Upregulation of PD-L1 by X-rays, and especially C-ions, may contribute to reduced immune cell activation, underscoring the need for combination strategies with immune checkpoint blockade. Collectively, our study highlights the NF-κB-driven immunostimulatory effects of autophagy inhibition and the importance of understanding the molecular heterogeneity in TNBC with regard to autophagy rates, IFN-I and NF-κB signaling when designing effective treatments that target these pathways.